Prehypertension in Rural Northeastern China: Results From the Northeast China Rural Cardiovascular Health Study. Issue 9 (6th August 2014) - Li, Zhao; Guo, Xiaofan; Zheng, Liqiang; Sun, Zhaoqing; Yang, Hongmei; Sun, Guozhe; Yu, Shasha; Li, Wenna; Zou, Lu; Wang, Jun; Hu, Wenyu; Sun, Yingxian
<x xml:space="preserve">Abstract</x> This study aimed to determine the present status of prehypertension in rural China. It was conducted between January and August 2013, using a multistage clustering method to select a representative sample of individuals (≥35 years old), resulting in a study population of 11, 576 adults. Prehypertension was defined as a systolic blood pressure (BP) in the range of 120 mm Hg to 139 mm Hg and/or a diastolic BP between 80 mm Hg and 89 mm Hg according to the Seventh Report of the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7). The results showed that the mean±standard deviation systolic and diastolic BP values for the entire population were 141.8±23.5 mm Hg and 82.1±11.8 mm Hg, respectively. Among the whole population, 35.1% of men and 32.5% of women were prehypertensive. Multiple logistic regression analysis showed that high body mass index, advanced age, alcohol consumption, diabetes, high triglyceride and low‐density lipoprotein cholesterol levels, and elevated diet score were risk factors for prehypertension. This study indicates that there is a high prevalence of prehypertension in rural China and confirms the importance of healthy lifestyles—including the control of obesity, diabetes, and dyslipidemia—to decrease the incidence of prehypertension.